ETIKA SOSIAL SANTRI MENUJU MODERNISASI PENDIDIKAN(TELAAH PENDIDIKAN SANTRI DI KUDUS) - Nasir, Amin (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
Pesantren world faced with the problems of globalization, which can be assured to contain responsibility which is not light for pesantren. Increasingly, the challenge of the pesantren world is getting bigger and harder in the present and future. The paradigm of